Adaptive Yoga - Yang, Ingrid 1979- (Human Kinetics, 2021)
"Adaptive Yoga is intended to teach yoga teachers and qualified healthcare professionals how individuals with chronic diseases and disabilities can maximize their yoga practice and recognize the healing and other benefits they can find with a consistent practice"--Provided by publisher.